Pengaruh Digital Marketing Development dan Etika Bisnis terhadap Competitive Advantage pada UMKM di Cikarang - Latifah Ayu Tiarani; Wita Supira; Arum Nur Fadillah; Dede Farida; Fitri Sri Khairunnisa; Retno Purwani Setyaningrum (Pusat Riset dan Inovasi Nasional, 2025)
This study explains the impact of digital marketing growth and business ethics on the competitive advantage of Micro, Small, and Medium Enterprises (MSMEs) in Cikarang. MSMEs have competed intensively in this digital era, so it is important to use innovative digital marketing and uphold business ethics to gain customer trust. However, most MSMEs in Cikarang still find it difficult to implement effective digital marketing strategies and business ethics in their daily operations, resulting in low competitive advantage. In the real world, this study uses a quantitative approach by distributing questionnaires to 60 MSME actors in Cikarang. The results show that the development of digital marketing and business ethics simultaneously have a significant influence on the competitive advantage of MSMEs. Although the role of digital marketing is significant, business ethics has a greater influence in shaping the competitive advantage of MSMEs in Cikarang. This means that MSMEs in Cikarang not only need to develop digital marketing, but also must prioritize business ethics to achieve sustainable competitive advantage..